2016
DOI: 10.1002/jso.24352
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model for resectable soft tissue and cutaneous angiosarcoma

Abstract: In the largest study to date of patients with angiosarcoma, risk factors for poor OS were identified to create a clinically useful risk model that can prognosticate patients with localized disease following surgical resection. J. Surg. Oncol. 2016;114:557-563. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 24 publications
7
55
4
Order By: Relevance
“…In the study from Japan of 260 cases of CAS, the 5-year overall survival among patients who could receive surgery was <20% ( 49 ) (median overall survival: < 20 months), whereas in the studies from western countries, it was 31–51% ( 5 , 11 , 25 , 31 , 40 ). CAS patients in Japan had equivalent survival to the “high risk” group reported by Sinnamon et al ( 32 ), with a median overall survival of 1.6 years. This difference might be explained by the fact that the tumor size in Japanese patients is generally large: in the study of 260 CAS cases, 44% of the patients had tumors of at least 10 cm (originally, described as tumors larger than 100 cm 2 ) ( 49 ), whereas tumors larger than 5 cm (T2) constituted only 18–38% of the patients in the studies from western countries ( 5 , 11 , 25 , 40 ).…”
Section: Prognosis and Factors Associated With Survivalmentioning
confidence: 60%
See 2 more Smart Citations
“…In the study from Japan of 260 cases of CAS, the 5-year overall survival among patients who could receive surgery was <20% ( 49 ) (median overall survival: < 20 months), whereas in the studies from western countries, it was 31–51% ( 5 , 11 , 25 , 31 , 40 ). CAS patients in Japan had equivalent survival to the “high risk” group reported by Sinnamon et al ( 32 ), with a median overall survival of 1.6 years. This difference might be explained by the fact that the tumor size in Japanese patients is generally large: in the study of 260 CAS cases, 44% of the patients had tumors of at least 10 cm (originally, described as tumors larger than 100 cm 2 ) ( 49 ), whereas tumors larger than 5 cm (T2) constituted only 18–38% of the patients in the studies from western countries ( 5 , 11 , 25 , 40 ).…”
Section: Prognosis and Factors Associated With Survivalmentioning
confidence: 60%
“…Generally, soft-tissue sarcomas have a 50–60% survival rate ( 30 ), whereas the 5-year survival rate for angiosarcoma is <40% ( 12 , 25 , 31 , 32 ). Several factors are reportedly associated with poor survival: older age ( 25 , 32 ), worse performance status ( 33 , 34 ), larger tumor size ( 5 , 8 , 20 , 32 , 35 40 ), positive margin status ( 31 , 32 , 38 , 41 , 42 ), higher histologic type or grade ( 32 , 37 , 41 , 43 , 44 ), scalp as the primary location ( 5 , 36 , 45 ), deeper location of the tumor ( 20 , 31 ), and presence of distant metastasis ( 33 , 38 , 41 , 46 ). On the other hand, the following factors were associated with favorable prognosis: surgery ( 20 , 34 ), multimodal therapy ( 5 , 39 , 41 ) and postoperative radiotherapy ( 34 , 36 , 41 , 43 , 47 , 48 ).…”
Section: Prognosis and Factors Associated With Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…In their meta-analysis, Shin et al [ 14 ▪▪ ] found that surgery improves the 5-year survival rate compared with other treatments [odds ratio (OR) = 4.369; P = .002]. Sinnamon et al [ 16 ] found that positive resection margins are associated with worse overall survival (OS). Curative surgery should always be considered for patients with cAS.…”
Section: Prognosis and Management Of The Diseasementioning
confidence: 99%
“…A study performed at the University of Texas MD Anderson Cancer Center demonstrated that patients who undergo combination therapy have statistically greater overall survival compared with those who undergo radiation or surgery alone 97. Histopathologically clear surgical margins are of paramount importance and correlate with better outcome 100. Although no clear guidelines exist on the specific width of surgical margins in cAS, achievement of 3 cm or greater clear margins as well as deep margins is recommended 5…”
Section: Current Treatment Recommendations and Undergoing Clinical Trmentioning
confidence: 99%